'There is no sincerer love than the love of food' (George Bernard Shaw, 1903): The meaning of food and its uses in prison subculture. (March 2019) - Einat, Tomer; Davidian, Moran
This study examines the ways in which the prison service handles food and analyses the uses and meanings of food in prison subculture. Using semi-structured interviews and content analysis, data were collected and analysed from 20 ex-prisoners who were incarcerated in maximum-security prison facilities for a period of three years or more. Our main findings are that, according to the interviewees' testimonies, (a) the Israel Prison Service (IPS) makes manipulative and abusive use of food in order to perpetuate its power; and (b) food serves as a means to determine the relationship between prisoners and staff, govern social status or rejection in the prison subculture, or pass the time. We have four main conclusions. First, the IPS nutrition policy differentiates and discriminates among prisoners and clearly violates the basic human rights of prisoners, thus suggesting an abuse of power. Second, the IPS's use of food as a tool for punishing or rewarding introduces and perpetuates inequalities and encourages the illegal prison trade in food and food products. Third, cooking in prison, especially in light of its illegality, constitutes a symbolic expression of resistance to the institution and a meaningful way of coping with boredom. Lastly, food and its possession in prison serve as very powerful tools for constructing and perpetuating exploitation and unequal power relations among prisoners. Although the study suffers from two limitations – the validity of the adolescents' responses and the small sample size – its findings lead us to propose that an improvement in the food products that are accessible to prisoners and permission to cook in their cells are inexpensive and legitimate means of bettering both the prisoners' quality of life and the social atmosphere in prison.